The consumer society - Goodwin, Neva R.; Ackerman, Frank; Kiron, David (Washington, D.C. : Island Press, 1997)
"The Consumer Society provides brief summaries of the most important and influential writings on the economic, environmental, ethical, and social implications of a consumer society and consumer lifestyles. It is an essential guide to the field and will interest anyone concerned with the deeper implications of consumerism. It is the second volume in the Frontier Issues in Economic Thought series, which provides surveys of the most significant writings in emergent areas of economics."--Jacket
pt. 9. Globalization and consumer culture -- Overview essay / Kevin Gallagher -- Development and the elimination of poverty / Nathan Keyfitz -- Third World consumer culture / Russell W. Belk -- Positional goods, conspicuous consumption, and the international demonstration effect reconsidered / Jeffrey James -- Advertising in nonaffluent societies : Galbraith revisited / Jeffrey James and Stephen Lister -- The culture-ideology of consumerism in the Third World ; The culture-ideology of consumerism in urban China / Leslie Sklair -- Transnational advertising : some considerations of the impact on peripheral societies / Noreene Janus -- Transnational corporations and Third World consumption : implications for competitive strategies / Rhys Jenkins -- Gross national consumption in the United States : implications for Third World development / Thomas Walz and Edward Canda -- pt. 10. Visions of an alternative -- Overview essay / Neva R. Goodwin -- Economic possibilities for our grandchildren / John Maynard Keynes -- Alternatives to mass consumption / Jerome M. Segal -- Exiting the squirrel cage / Juliet Schor -- How to bring joy into our economics / Tibor Scitovsky -- Qualitative growth / Fred Block -- The poverty of affluence : new alternatives / Paul Wachtel -- A culture of permanence / Alan Durning -- Living more simply and civilizational revitalization / Duane Elgin -- Subject index -- Name index.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Consumer behavior -- Social aspects -- United States; Consumption (Economics) -- Social aspects -- United States; Consommateurs -- Comportement -- Aspect social -- États-Unis.; Consommation (Économie politique) -- Aspect social -- États-Unis.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Consumer behavior -- Social aspects; Consumption (Economics) -- Social aspects; United States; Consumptiemaatschappij; Consommation -- Attitudes -- Aspect social -- États-Unis.; Consommation -- Aspect social -- États-Unis.; Consommateurs -- Attitudes; Aufsatzsammlung -- USA -- Konsumgesellschaft -- Geschichte; Aufsatzsammlung -- USA -- Verbraucherverhalten -- Geschichte